Pesquisa de Staphylococcus spp. em superfícies inanimadas e no ar de uma unidade de terapia intensiva neonatal - Silva, Felipe Flávio (2020)
Introduction: Environmental and air contamination plays an important role in the transmission of infections related to health care. Staphylococcus spp. they are often detected in the hospital environment because they are resistant to environmental changes, with the ability to survive months in these places. Objectives: To verify the presence of Staphylococccus spp. and multidrug resistant Staphylococccus on inanimate surfaces, air and neonates of the Neonatal Intensive Care Unit of the Hospital of Clinics of the Federal University of Uberlândia (HC-UFU) and additionally analyze the risk factors for infections through an epidemiological surveillance to monitor hospitalized neonates during the study period. Methods: The samples of the environment were collected with a sterile swab moistened with sterile 0.9% saline and for air samples, TSA plates were exposed in the center of the unit at 1m from the floor, 1m of obstacles for 1h. The bacteria were identified by MALDI-TOF MS and the Antimicrobial Susceptibility Test by diffusion disk was performed. All neonates were monitored daily by epidemiological surveillance. Results: Of the 408 samples of collected environmental surfaces, 93 (22.8%) presented contamination by Staphylococcus spp., With the incubators and the support table for the monitors, the places that presented the highest percentage. Of the nine plates exposed for air collection, all showed growth. Of the total isolates, 61 (55%) were multidrug resistant. Surveillance included 246 neonates admitted to the unit during 2018, 50 with infection by Staphylococcus spp., Totaling 78 isolates. Final considerations: It is relevant to assess the role of the environment in infections, especially in critical units, for proposing strategies that reduce contamination and the spread of pathogens.